Improving methane production from food waste by intermittent agitation: Effect of different agitation frequencies on solubilization, acidogenesis, and methanogenesis. (September 2022) - Sekine, Mutsumi; Mizuno, Naoki; Fujiwara, Masaaki; Kodera, Toshimitsu; Toda, Tatsuki
Abstract: The intermittent agitation system is effective in reducing energy consumption during anaerobic digestion of organic waste. However, insufficient agitation leads to a significant reduction in reactor performance. Therefore, it is necessary to clarify the organic degradation reactions that are limited or accelerated by agitation to ensure proper agitation. This study aimed to investigate the effects of different agitation frequencies on solubilization, acidogenesis, and methanogenesis. Food waste, which is a relatively easily degradable and common substrate for anaerobic digestion, was treated in a mesophilic batch operation under continuous, intermittent (15 min every 6, 12, and 24 h), or no agitation conditions. The highest cumulative CH4 yield of 339 NmL g-COD −1 was obtained under intermittent agitation once every 12 h, followed by 306 and 304 NmL g-COD −1 under continuous agitation and once per 6 h agitation, respectively. However, lower agitation conditions (once per 24 h and no agitation) showed lower methane yields. Based on the mass balance of chemical oxygen demand, the solubilization efficiency tended to be high under high agitation frequency. Furthermore, the highest acidogenesis and methanogenesis efficiencies were obtained under once per 12 h agitation. The number of microbial cells and the relative abundance of hydrogenotrophic methanogens that work with H2 producing bacteria decreased, likely due to agitation stress. A once per 12 h agitation was sufficient to promote solubilization and avoid agitation stress on microorganisms in the food waste treatment. Moderate intermittent agitation is a promising method for maximizing CH4 recovery and minimizing energy consumption. Highlights: 1. Mixing frequency is optimized to digest easily degradable food waste. 2. Highest CH4 production is achieved in intermittent agitation every 12 h. 3. Less and more mixing suppresses solubilization and acid/methanogenesis, respectively. 4. Mixing breaks microbial symbiosis, but microbes can maintain CH4 yield. 5. Optimum intermittent agitation maximizes CH4 recovery with less energy consumption.